The Australian nexus at the center of the storm - Doyle, Randall Jordan (Lexington Books, 2018)
"This book is about Australia finding its way in the Indo-Pacific during extraordinary times. Australians are trying to grasp the varied geopolitical dynamics that represent the fundamental elements of a historic epoch that is reconfiguring Australia's future path within this vast region of the world"--